Proposi????o de um artefato para gerenciamento de projetos de lan??amento de produtos ou servi??os das startups - Santos, Everton Bispo dos (2019)
In turn, nine out of ten startups fail, whether due to lack of business acumen, ability to model the business, lack of maturity for conflict resolution or lack of management skills. This last reason is related to project management skills. Currently, companies that go through the startup phase have about 70% of their activities in projects and 30% in day-to-day operation, which shows us the relevance of projects. Startups are gaining more fans and enthusiasts every day, as well as fostering and bringing about big changes in the entrepreneurship landscape. In all major economies of the world, especially Brazil, investments in startups are increasingly relevant and expressive. The interest in startups is from young graduates to experienced investors who understand that innovation and agility in developing a product is essential to the moment we live. To support and structure these projects, project management (GP) approaches are implementing serious improvements to meet this new scenario. This new scenario, which involves technology, innovation and agility, requires new models that meet these requirements. Given this, the purpose of this research is the proposition of a GP artifact for launching products or services of startups. For this research we used the Design Science Research (DSR) method to identify the problem of lack of project management in startups and to develop an artifact that solves it. The identification of the problem included a literature review and 6 interviews with founders of startups. To evaluate this artifact in practice and validate its adherence and effectiveness, we used the research-action research method in a startup, in the application of an online course launch project. The projected artifact consists of a canvas, with sections that summarize the iron triangle, with fields for planning and controlling scope, time, cost and human resources. The purpose of this artifact is to support startups in managing their product or service launch projects. The results promote the artifact's practical contribution to startups who need a simple and effective GP support model because the learning curve is relatively low.